Analisis Kinerja Kebijakan Bupati dalam Pengangkatan Tenaga Honorer di Pemerintah Kabupaten Badung - I Wayan Arta; A.A. Gede Raka; I Made Sumada (Universitas Warmadewa, 2019)
Abstract The appointment policy of honorary staff is embodied in the form of Badung Regent Decree Number: 1316 / 01 / HK / 2005 concerning the Appointment of Honorary Staff in Badung Regency Government whose number has reached 102 people, this is expected to be able to increase policy performance maximally. But in reality the work program has not been intended as expected. Problems have been occurred What is the performance of the Bupati's policy in the appointment of honorary staff in the Badung Regency Government and what factors have led to the ineffective performance of the Regent's policies in the appointment of honorary staff in Badung Regency Government. This research method uses a qualitative descriptive approach. The theory which is used is the theory of policy analysis to be proposed by Dunn and the theory of failure factors according to Hoogewerf. The results of this study has found that the achievement of the performance of honorary staff that has not been maximized due to the lack of support from leadership in the development of Human Resources honorary staff. For this reason, it is recommended that the leadership of honorary staff in each regional apparatus improve their performance and need to be given the opportunity for education and training at least 20 lessons per year according to the mandate of Law No. 5 the Year 2014 and PP No. 11 the Year 2017. Abstrak Kebijakan pengangkatan tenaga honorer dituangkan dalam bentuk Surat Keputusan Bupati Badung Nomor : 1316/01/HK/2005 tentang Pengangkatan Tenaga Honorer di Lingkungan Pemerintah Kabupaten Badung yang jumlahnya mencapai 102 orang, ini diharapkan mampu untuk meningkatkan kinerja kebijakan secara maksimal. Namun dalam kenyataannya progam kerja belum terwujud sesuai dengan harapan. Permasalahan yang terjadi Bagaimana kinerja kebijakan Bupati dalam pengangkatan tenaga honorer di Pemerintah Kabupaten Badung dan faktor-faktor apa yang meyebabkan belum efektifnya kinerja kebijakan Bupati dalam pengangkatan tenaga honorer di Pemerintah Kabupaten Badung. Metode penelitian ini menggunakan pendekatan deskreptif kualitatif. Teori yang digunakan adalah teori analisis kebijakan yang dikemukakan oleh Dunn dan Teori faktor-faktor kegagalan menurut Hoogewerf. Hasil dari penelitian ini menemukan capaian kinerja tenaga honorer belum maksimal ini disebabkan kurangnya dukungan dari pimpinan dalam pengembangan Sumber Daya Manusia tenaga honorer. Untuk itu disarankan kepada pimpinan tenaga honorer di masing-masing perangkat daerah untuk memperbaiki kinerjanya perlu diberikan kesempatan pendidikan dan pelatihan minimum 20 jam pelajaran per tahun sesuai amanat UU No. 5 Tahun 2014 dan PP No. 11 tahun 2017.